Just start : take action, embrace uncertainty, create the future - Schlesinger, Leonard A.; Kiefer, Charles F.; Brown, Paul B. (Boston, Mass. : Harvard Business Review Press, 2012)
Outlines a path to success based on creativity and problem solving despite the changing economic clmate and future uncertainty.
Introduction : Navigating uncertainty -- Part I. What to do when facing the unknown : What to do when you can't predict the future -- The overwhelming importance of desire -- Part II. What to do when you take action in the face of uncertainty : Act quickly with the means at hand -- Assess your acceptable loss -- Build on what your find -- Bring other people along -- Part III. How this works in the real world : View the future along a continuum: when to use prediction and when to use creaction -- Prepare for uncertainty: how to use creaction at work -- Using creaction with families and friends -- How creaction can make a better world -- Epilogue : Responses to some challenging comments and questions we receive.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Success in business; Creative ability in business; Problem solving; Success; Creative ability; Problem solving; Business; Gestion du risque; Creative ability in business; Problem solving; Success in business; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books